2014
DOI: 10.25077/jif.6.1.36-39.2014
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pergeseran Mikro Menggunakan Sensor Serat Optik Fd 620-10

Abstract: Telah diperoleh sensitivitas sensor serat optik untuk pengukuran pergeseran mikro. Pergeseran mikro diukur dengan menggunakan metode sensor serat optik ekstrinsik. Susunan sistem sensor serat optik terdiri dari serat optik produksi autonics tipe FD 620-10, laser dioda dengan πœ† = 650 π‘›π‘š, dan fotodetektor OPT101. Sensitivitas tertinggi berada pada jarak 1 mm sampai 2 mm yakni sebesar 2,506. Maksimum pengukuran pergeseran mikro yang dapat dipakai adalah 3 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Previous research analyzed the micro-shift using a fiber optic sensor. The characterization results showed that the best distance between the optical fiber and the reflector was at a distance of ≀5cm (Saputro et al, 2014). The reflector that provides the highest output voltage is a brass plate of 270 mV, which is used as a reflector in tool development.…”
Section: Fiber Optic Sensor Characterization Resultsmentioning
confidence: 99%
“…Previous research analyzed the micro-shift using a fiber optic sensor. The characterization results showed that the best distance between the optical fiber and the reflector was at a distance of ≀5cm (Saputro et al, 2014). The reflector that provides the highest output voltage is a brass plate of 270 mV, which is used as a reflector in tool development.…”
Section: Fiber Optic Sensor Characterization Resultsmentioning
confidence: 99%